Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have already worked out a lot of stuff already from previous parts of the questions and I think I've got to work from the fact that $a_{2k+1}=0$ and $a_{2k}= (-1)^k/k!$ for k>0 satisfies the recurrence relation of the power series as it states this and then says hence deduce that $y(x)=e^{-x^2}$

share|cite|improve this question
up vote 0 down vote accepted

$$e^x = \sum^{+\infty}_{k=0}\cfrac {x^k}{k!} \implies e^{-x^2}=\sum^{+\infty}_{k=0}\cfrac {(-x^2)^k}{k!}=\sum^{+\infty}_{k=0}\cfrac {(-1)^k}{k!}x^{2k}$$ The coefficient of $x^{2k}$ satisfies the sequence you found.

Working forward

$$\sum^{+\infty}_{k=0}a_k\ x^k =\sum^{+\infty}_{k=0}a_{2k}\ x^{2k}+\sum^{+\infty}_{k=0}a_{2k+1}\ x^{2k+1}=\sum^{+\infty}_{k=0}\cfrac {(-1)^k}{k!}\ x^{2k}=\sum^{+\infty}_{k=0}\cfrac {(-x^2)^k}{k!}=e^{-x^2}$$

share|cite|improve this answer

The only thing you have to do is to show that $f(x)=e^{-x^2}$ satisfies the equation with the initial values. By the existence and uniqueness theorem for ode, you will know that this is the solution.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.